PREFORMULATION STUDIES USING LACTOSE IN DEVELOPMENT OF SOLID ORAL DOSAGE FORM: A GRAPHICAL REPRESENTATION USING SeDeM METHOD - Tadwee, Imran; Shahi, Sadhana; Zaheer, Zahed (International Journal of Current Pharmaceutical Research, 2017)
Objective: The objective of the study is to evaluate and present lactose scientifically as an excipient of choice in formulation development of solid orals dosage form for direct compression method. Present work will establish the ability of lactose as an excipient to be the choice of candidate while developing formulation having poor flow API using direct compression process. In addition to this different type of lactose is processed using secure development method (SeDeM) in order to evaluate best suitable type of lactose amongst its different type. Methods: Lactose anhydrous, lactose monohydrate and Lactose spray dried (SD) were employed for evaluation using SeDeM method, twelve different selected pharmacotechnical parameters were determined experimentally and were treated mathematically and expressed in the graphical representation as SeDeM diagram. Parameter index, parameter profile index and good compression index values were calculated. Results: Good compression index was found to be 6.06,5.72,6.83 parameter index was 0.25, 0.42, 0.17 and parameter profile index found to be 6.36,6.01,7.18 for lactose anhydrous, lactose monohydrate and Lactose SD respectively. Conclusion: This research work reveals that data obtained will be useful for the pharmaceutical industries while formulating the drug product and will reflect the scientific characteristics of this excipient as well. This will enable the availability of values obtained after performing SeDeM studies on lactose to scientific society based on the results researchers can use establised data and statistics in their pre-formulation studies to incorporate lactose with confidence and can be justified scientifically in the development formulation of the direct compression process and API having poor flow. Results indicating good direct compression characteristics of the all 3 type of lactose, and Lactose SD can be preferred amongs these 3 types. Â 